Identifying and categorising profane words in hate speech - Teh, Phoey Lee *; Cheng, Chi-Bin; Chee, Weng Mun (2018)
This study attempts to explore the different types of Hate Speech appearing in social media by identifying profane words used in hate speech. This study also compares the profane words used in different generations to assist in identifying the user's profile. Five-hundred (500) comments posted on YouTube on the abusive topics were collected. Profane words are classified into eight different types of hate speech. The finding shows 35% of profane words found in our sample are words related to sexual orientation. Comparison of the terms between 1970 and 2017 also show a high percentage of profane words are sexual orientation. Though the results are found based on only 500 comments collected from YouTube link in the current study, they are useful in establishing the list of profane words which will serve as the base for automatic hate speech identification in our future study. The originality of this research is the development of a training list of profane words for each category and comparison of the type of the words used in 1970 century with today's social media platform.